Martin luther king jr: civil rights hero - Claybourne, Anna (Wayland, 2002)
This book looks at the life of Martin Luther King, whose message of peace changed American history. Born in 1929, King was a Baptist preacher who went on to fight racism and segregation in an unfair American society